Analysis of the theme bullying in feminine magazines for teens - Ana Cláudia Bortolozzi Maia; Marcela Pastana (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
Practices of violence such as physical and verbal aggression, provocations, humiliations and exclusion that occur mainly among young people in schools are named as bullying and the aim of this qualitative-descriptive study was to investigate how this phenomenon is represented by magazines directed to teenage girls. The analysis was conducted in fifteen articles of four Brazilian magazines: Capricho, Todateen, Atrevida and Yes Teen through thematic categories: 1) Definitions and explanations about bullying; 2) Magazines' proposals to the confrontation against bullying (2.1 Campaigns and orientations against bullying; 2.2 Advices about how to act in the presence of bullying; 2.3 Examples of "overcoming" to people who suffered bullying and 2.4 Advices given to people who practice bullying). It was identified the presence of hierarchies, stereotypes and the incentive to competition. There is the predominance of normative and excluding patterns, advices that individualize the issue and lack of critical reflection.